Blue Ocean Strategy, Expanded Edition - Kim, W.; Mauborgne, Renee (Ascent Audio, 2020)
In this perennial bestseller, embraced by organizations and industries worldwide, globally preeminent management thinkers W. Chan Kim and Renee Mauborgne challenge everything you thought you knew about the requirements for strategic success. Recognized as one of the most iconic and impactful strategy books ever written, Blue Ocean Strategy, now updated with fresh content from the authors, argues that cutthroat competition results in nothing but a bloody red ocean of rivals fighting over a shrinking profit pool. Based on a study of 150 strategic moves (spanning more than 100 years across thirty industries), the authors argue that lasting success comes not from battling competitors but from creating "blue oceans"-untapped new market spaces ripe for growth. Blue Ocean Strategy presents a systematic approach to making the competition irrelevant and outlines principles and tools any organization can use to create and capture their own blue oceans. This expanded edition includes: a new preface by the authors: "Help! My Ocean Is Turning Red"; updates on all cases and examples in the book; and two new chapters and an expanded third one-"Alignment, Renewal, and Red Ocean Traps"-that address some of the most pressing questions readers have asked over the years.